According to the Turkish archive resources: helps of Hungarians to the ottoman redcrescent association during the First World War : Yücel Namal - Namal, Yücel (Közép-Európai Közlemények, 2014)
Hungarians have helped to the Red Crescent Association during the First World War as being during the Balkans War. The Ottoman Red Crescent Association had bought the health and medical stuffs (gaseous hydrophilic, cotton hydrophilic, stretcher, dressing packages, gauze bandage, antipyretic) from Hungary many times during the First World War. During the War, the health care teams, consisting of the Hungarian physicians, nurses and caregivers had served to the Ottoman Red Crescent Association in Istanbul and other Ottoman cities. In addition, since Turks and Hungarians were traditional and historical friends, and the Hungarians were allies during the First World War, in order that Hungarians presented their appreciation, they had passed the hat in many Hungarian cities and had donated it to the Ottoman Red Crescent Association. The Hungarian Prime Minister, Count István Tisza, had provided the significant encouragement and support for passing the hat. The municipal committees of the Hungarian cities (Esztergom, Fejer, Nagy Varad and Györ) presented their sincere greetings to the Ottoman nation that was the loyal ally of Hungarian nation, and the greetings from Istanbul city was also presented to the Hungarian brothers. The aids from Hungarians to the Ottoman Red Crescent were encouraged through the announcements in the Hungarian newspapers. Furthermore, the aids to the Ottoman Red Crescent were increased gradually through the concerts and exhibitions that were organized by the Hungarians. The Hungarians stated especially that these aids were provided by the Hungarian people, the Austria should have been exempted due to the dual monarchy and it should have been stated in the announcements for appreciating in the newspapers that the aids were provided by Hungarians only. During the War, the Hungarians helped to the Turks as if competing with Austria. In this case, the Ottoman Government thanked the Hungarians who helped to the Red Crescent Association by awarding the medals.